Leaf litter lignin degradation in response to understory vegetation removal in a Masson pine plantation. (28th December 2020) - He, Wei; Keyhani, Abdul Baess; Ma, Zhiyuan; Xu, Jiaoyang; Zhang, Chenchen; Xu, Xin; Teng, Mingjun; Yan, Zhaogui; Wang, Ben; Wang, Pengcheng
Abstract: Understory vegetation changes, caused by forestry management, can alter the litter species composition and microclimate in situ, which while profoundly influence litter lignin degradation processes, is seldom investigated. To reveal the effects of these changes, understory vegetation in plots was treated as follows: no understory vegetation removal; only shrub removal; only herb removal; and, both shrub and herb removal. Single‐ and mixed‐species litterbags (1.0 mm mesh with uncut leaf litter) matching the treated vegetation characteristics (complied with a 7:2:1 air‐dried mass ratio for the litter form trees, shrubs, and herbs) were placed on the floor. After 2 years, 5.9% (single‐tree litter in the plots with shrub removal) to 41.4% (mixture in the plots with no understory vegetation removal) of the initial lignin content was degraded among litterbag types and plot treatments. Incidence of nonadditive effects was reduced, and the nonadditive lignin degradation rate varied but remained low among plot treatments when understory vegetation was removed. In all plot treatments, lignin degradation rate was higher in single‐shrub or single‐herb litter than in single‐tree litter (at least 9.7% ± 1.2% for the deviation). Mixtures in the plots, with no understory vegetation removal, exhibited a greater lignin degradation rate than that of the litter mixtures in the other plots. Path analysis indicated that microbial biomass nitrogen, average temperature, and lignin concentration were positively correlated with lignin degradation rate. Therefore, in addition to the litter species composition, alterations in microclimate as a result of understory vegetation changes can be a key factor that influence lignin degradation rate.